Tenfibgen-DMAT Nanocapsule Delivers CK2 Inhibitor DMAT to Prostate Cancer Xenograft Tumors Causing Inhibition of Cell Proliferation - Trembley, Janeen H. (Mol Cell Pharmacol, 2014)
CK2 is a master regulator protein kinase which demonstrates heightened expression in diverse cancer types and is considered a promising target for therapy. Given its ubiquitous expression and potent influence on cell survival, cancer cell-directed targeting of the CK2 signal is an important factor for development of an anti-CK2 therapeutic. We previously reported on the malignant cell specificity and effect on CK2 signaling of a tenfibgen (TBG) based nanocapsule for delivery of the CK2 small molecule inhibitor 2-dimethylamino-4,5,6,7-tetrabromo-1H-benzimidazole (DMAT) in cultured prostate cancer cells. Here we tested the ability of TBG-DMAT to affect the growth of prostate xenograft tumors in mice. Our results show that treatment of PC3-LN4 xenograft tumors with TBG-DMAT caused loss of proliferative Ki-67 signal as well as Nuclear Factor-kappa B (NF-κB) expression in the tumors. Further, the TBG-DMAT nanocapsule was detected in tumors and not in liver or testis. In conclusion, TBG-based nanocapsule delivery of anti-CK2 small molecule drugs holds significant promise for treatment of prostate cancer.